The effect of high-temperature on concrete properties and the role of waste pozzalanic material to increase concrete resistance, A review - Jamel, Amer; Hama, Sheelan (Iraqi Journal of Civil Engineering, 2024)
The performance of the structural materials (concrete and steel reinforcement) and the behavior of the structural members after they were exposed to high temperatures have been considered the main topics of the current literature review. All varieties of concrete mixtures lost their compressive strength after 300˚C, even though there was no discernible strength loss between 150 and 300˚C. It was also discovered that the heating time had no appreciable impact on the strength loss when the exposed to heat less than 300 ˚C. Above 300 ˚C. Concrete begins to lose strength after being exposed for longer than one hour; the greatest loss of strength occurs during the first and second hours of exposure. Both the cured cement paste and the aggregates undergo chemical and physical changes at temperatures ranging from 600 °C to 900 °C. The 5% weighted rice husk ash (RHA) blended concrete still had an advantage in compressive strength, over the concrete when subjected to temperatures up to 700 C for two hours. Adding more recycled glass and ceramic particles to regular concrete increases its overall compressive and tensile strengths. Concrete becomes more durable and has fewer cracks when there is a higher replacement rate for ceramic and glass particles. The splitting tensile strength decreased with increasing temperature, changing from 60% to 70% of its initial strength after 600 °C. In this review, the better performance of concrete than the other concrete in terms of mechanical, physical, and durability properties at both room temperature and high temperature were concrete with 10% waste glass powder (WGP) substitution as a partial of cement and 10%–20% crushed glass (CG) substitution as a partial of aggregate .